Natural pyrethrins induces apoptosis in human hepatocyte cells via Bax- and Bcl-2-mediated mitochondrial pathway. (25th January 2017) - Yang, Yun; Zong, Mimi; Xu, Wenping; Zhang, Yang; Wang, Bo; Yang, Mingjun; Tao, Liming
Abstract: Natural pyrethrins have been widely used for pest control in organic farming and for residential indoor pest managements. Although the specific mechanisms underlying their activity are incompletely understood, natural pesticides are considered the safest based on their target specificity and rapid degradation in the environment. Here, we used in vitro bioassays to characterize the cytotoxic effects of natural pyrethrins and attempted to delineate the cellular and molecular mechanisms of their cytotoxicity against human hepatocytes. The results demonstrate that natural pyrethrins reduce cell viability and enhance apoptosis in HepG2 cells. In addition, the current data indicate that natural pyrethrins cause a reduction in the mitochondrial membrane potential ( Δψm ), increase reactive oxygen species production, and up-regulate the Bax/Bcl-2 expression, leading to the release of cytochrome- c into the cytosol, activation of caspase-9 and caspase-3 and cleavage of poly (ADP-ribose) polymerase (PARP). Taken together, the results indicate that natural pyrethrins has potentially exert adverse effects on human health by inducing caspase-dependent apoptosis in hepatocytes through Bax- and Bcl-2-mediated mitochondrial pathway. Highlights: Natural pyrethrins has potential threats to human health. Natural pyrethrins has significant cytotoxicity to Human hepatocyte cells in vitro. Natural pyrethrins induces caspase-dependent apoptosis in HepG2 cells through Bax- and Bcl-2-triggered mitochondrial pathway.